Recruitment and retention strategies of LIS students and professionals from underrepresented groups in the United States. Issue 2 (27th February 2020) - Harper, Lindsey M.
Abstract : Purpose: The American Library Association has worked for decades to increase its diversity of individuals from underrepresented groups; however, existing diversity programs in the United States yield just enough new library and information science professionals to replace those retiring or leaving the profession prematurely. Design/methodology/approach: This paper involved performing a review of the literature to assess recruitment and retention strategies of individuals from underrepresented groups within the LIS profession. Findings: This article examines the problems with existing diversity initiatives within the profession and suggests how the field can recruit both students and employees from underrepresented groups. This article offers new ways to recruit students and employees (e.g. how to create job postings and interview questions) and speaks about strategies for retaining LIS students and employees from underrepresented groups (e.g. formal and informal mentoring networks). Finally, this article offers some suggestions to create a more inclusive environment for LIS students and professionals alike. Originality/value: This paper offers practical suggestions to increase representation of individuals from underrepresented groups that LIS programs and libraries alike can implement. Suggestions for how to create an inclusive work environment are also presented.